2023
DOI: 10.48550/arxiv.2302.09668
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Physics-aware deep learning framework for linear elasticity

Abstract: The paper presents an efficient and robust data-driven deep learning (DL) computational framework developed for linear continuum elasticity problems. The methodology is based on the fundamentals of the Physics Informed Neural Networks (PINNs). For an accurate representation of the field variables, a multi-objective loss function is proposed. It consists of terms corresponding to the residual of the governing partial differential equations (PDE), constitutive relations derived from the governing physics, variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…More recently, deep learning (DL) characterized by multilayer neural networks (NN) (LeCun et al, 2015) has shown remarkable breakthroughs in pattern recognition for various fields including image classification (Rawat and Wang, 2017;Khan et al, 2022b,a), computer vision (Voulodimos et al, 2018;Roy and Bhaduri, 2021;Roy et al, 2022c;Roy and Bhaduri, 2022;Roy et al, 2022a), object detection (Zhao et al, 2019a;Chandio et al, 2022;Roy et al, 2022b;Singh et al, 2023a), brain-computer interfaces (Roy, 2022b,a,c;Singh et al, 2023b), signal classification Roy, 2023, 2022) and across diverse scientific disciplines (Bose and Roy, 2022;Roy and Bose, 2023b;Roy and Guha, 2022;Roy and Bose, 2023a;Roy and Guha, 2023). Following the success, there is an increasing thrust of research works geared towards damage classification tasks employing DL techniques, mostly convolutional neural networks (CNN), such as ResNet (Bang et al, 2018), AlexNet (Dorafshan et al, 2018;Li et al, 2018), VGG-net (Gopalakrishnan et al, 2017;Silva and Lucena, 2018) and various others (Chow et al, 2020;Nath et al, 2022;.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, deep learning (DL) characterized by multilayer neural networks (NN) (LeCun et al, 2015) has shown remarkable breakthroughs in pattern recognition for various fields including image classification (Rawat and Wang, 2017;Khan et al, 2022b,a), computer vision (Voulodimos et al, 2018;Roy and Bhaduri, 2021;Roy et al, 2022c;Roy and Bhaduri, 2022;Roy et al, 2022a), object detection (Zhao et al, 2019a;Chandio et al, 2022;Roy et al, 2022b;Singh et al, 2023a), brain-computer interfaces (Roy, 2022b,a,c;Singh et al, 2023b), signal classification Roy, 2023, 2022) and across diverse scientific disciplines (Bose and Roy, 2022;Roy and Bose, 2023b;Roy and Guha, 2022;Roy and Bose, 2023a;Roy and Guha, 2023). Following the success, there is an increasing thrust of research works geared towards damage classification tasks employing DL techniques, mostly convolutional neural networks (CNN), such as ResNet (Bang et al, 2018), AlexNet (Dorafshan et al, 2018;Li et al, 2018), VGG-net (Gopalakrishnan et al, 2017;Silva and Lucena, 2018) and various others (Chow et al, 2020;Nath et al, 2022;.…”
Section: Introductionmentioning
confidence: 99%